리스프랑 관절 골절 및 탈구: 나사와 Kirschner 강선을 이용한 치료 - 하동준; 김전교; 곽희철; 장의찬; Ha, Dong-Jun; Kim, Jeon-Gyo; Gwak, Heui-Chul; Jang, Yue-Chan (대한족부족관절학회지, 2015)
Purpose: The purpose of this study is to retrospectively analyze the clinical results of screws and Kirschner wire (K-wire) fixation in patients with fracture dislocation of Lisfranc joint and the consequence of screw breakage. Materials and Methods: Sixty patients underwent Lisfranc joint open reduction and removal of internal fixators from January 2007 to December 2011. Forty-nine cases (81.7%) underwent operations with screw alone, and 11 cases (18.3%) underwent operations with both screws and K-wires. Type of internal fixators, duration of internal fixator removal, breakage of internal fixators and satisfaction with reduction were investigated. Additionally, American Orthopaedic Foot and Ankle Society (AOFAS) midfoot scales were analyzed. Results: The internal fixator was broken in 5 cases (8.3%). The average duration of instrument removal was 154 days in the non-broken screw group and 268.6 days in the broken screw group (p<0.05). The average AOFAS midfoot scale was 77.4 in the non-broken screw group and 74.2 in the broken screw group. The most commonly damaged portion was the first tarsometatarsal (Lisfranc) joint. Conclusion: Treatment with screws and K-wires was effective in patients with fracture dislocation of Lisfranc joint. The appropriate time for screw removal should be considered.